Invariant and variable base stacking geometries in B-DNA and A-DNA - Neugebauerová, S; Kypr, J (Journal of biomolecular structure & dynamics, 2000)
We calculated the interatomic distances between all couples of non-hydrogen atoms belonging to the neighboring Watson-Crick base pairs in the available crystal structures of DNA. Their standard deviations revealed remarkably large differences in the variability of the base stacking geometries of the particular steps. In line with experimental studies in solution, (CpA)-(TpG) and (TpA).(TpA) were identified as the most variable or flexible steps in the crystal structures of B-DNA. On the other hand, base stacking geometries of the (ApT).(ApT) steps were the most invariant, which was very surprising because all three steps composed only of C and G were much more flexible. This finding suggests that conformational stability of DNA and the rigidity have different origins. Furthermore, the nucleotide sequence dependence of the flexibility was almost reversed in A-DNA because the most flexible steps in B-DNA were the least flexible in A-DNA. The most invariant steps of B-DNA were variable in A-DNA. The (ApT).(ApT) step was a notable exception to this rule because it belonged to the most rigid steps in both B-DNA and A-DNA. The present results are fully consistent with the properties that poly(dA-dT).poly(dA-dT), poly(dA).poly(dT), poly(dAdC).poly(dG-dT) and poly(dA-dG).poly(dC-dT) exhibit in solution.
Keywords: polydeoxyribonukleotidy; Crystallography, X-Ray; DNA; sekvence nukleotidů; konformace nukleové kyseliny; krystalografie rentgenová; Base Sequence; Nucleic Acid Conformation; párování bází; Polydeoxyribonucleotides; Base Pairing